Research on Elevated Temperature Mechanical Properties and Microstructure of Mg-50Ti Composite - LI Shi-tian; ZHAO Si-cong; MA Tao; GUO Er-jun; LIU Kun; ZHANG Dao-he; WANG Lei; FENG Yi-cheng; LIU Dong-rong (Journal of Harbin University of Science and Technology, 2022)
Abstract:Powder metallurgy was used to prepare Mg-50Ti composite with excellent elevated temperature mechanical properties. Tensile testing machine was used to test the room temperature and elevated temperature properties of the composite. The optical microscope and scanning electron microscope were used to analyze the microstructure and observe the fracture morphology. The results show that the Mg-50Ti composite achieved excellent elevated temperature mechanical properties at 200℃. Its ultimate tensile strength and elongation after fracture are 97.6 MPa and 1.2%, respectively. The tensile strength is only 5% lower than that at room temperature. As the tensile test temperature increased, the tensile strength of the composite gradually decreased, the elongation after fracture gradually increased, and the elastic modulus gradually decreased. The fracture surface of the composite under all tensile temperature is brittle fracture. The fracture mechanism includes Mg matrix cracking, reinforcement Ti particles fracture, Mg matrix and reinforcement Ti particles interface debonding. The failure fracture below 200℃ is due to the fracture of the Mg matrix and Ti particles. While the fracture mechanism of the failure fracture over 200℃ gradually transforms into the fracture of the Mg matrix, the debonding of the interface between the reinforcement and the matrix leads to the failure of the composite.